Comparative analysis of the bail-in tool - Jakub Kerlin; Anna Maksymiuk (Copernican Journal of Finance & Accounting, 2015)
The article aims to analyse selected components of one of the tools of orderly restructuring and liquidation of financial institutions, namely the conversion of equity or debt write-down tool (bail-in). The presented breakdown shows the variety of approaches to defining bail-in and points of convergence of these approaches. One of the key findings highlights the global shift in the approach to the issue of restructuring and liquidation of financial institutions and indicates a new path undertaken by public authorities, which allows for allocating costs to the owners of financial institutions. Governments should prepare a legal framework for the effective use of this tool before the necessity of its application becomes manifest. The study is based on a comparative review of legal frameworks in selected countries as well as reports, studies, publications and practical experience of countries that have applied bail-in.